Telemedicine in Remote Areas: An Innovative Solution for Equal Access to Healthcare Services - Firayani Firayani; Seno Lamsir (PT. Anagata Sembagi Education, 2025)
Telemedicine has emerged as an innovative solution to address inequities in healthcare access in remote regions, particularly in developing countries facing geographical constraints and uneven distribution of health workers. This study aims to provide a comprehensive analysis of how telemedicine can support equitable healthcare delivery through an evidence-based systematic approach. Using a PRISMA-guided Systematic Literature Review (SLR), the study synthesized 54 eligible articles identified from 412 publications. The findings indicate that the effectiveness of telemedicine is strongly influenced by digital infrastructure readiness, healthcare workforce competence, socio-cultural acceptance, and policy sustainability. Persistent challenges including unstable connectivity, low digital literacy, workforce overload, and fragmented governance continue to hinder optimal deployment in remote settings. The study concludes that telemedicine can serve as a viable equity-enhancing tool only when structurally integrated into the health system, supported by strategic investments in infrastructure, continuous professional training, and community-centered implementation models. These findings offer a foundation for developing more inclusive and sustainable digital health transformation strategies